(untitled) (Contemporary Journal of Social Science Review, 2025)
Speaking English is now a mandatory academic and professional aspect among university students especially in countries where English is not the first language like in Pakistan. Nonetheless, a lot of students have difficulties in speaking fluently because of psychological and cognitive challenges. This paper explores the interaction between anxiety and cognitive load in the performance of the English speaking students in the university level. This study is informed by the constructs of the Attitude/Motivation Test Battery (AMTB) by Gardner to examine the effect of emotional factors, mental effort, and instructional conditions on the fluency, accuracy, and confidence of spoken English. Ten university students in various semesters were interviewed using a qualitative research design approach where semi-structured interviews were used. The results show that the anxiety related to language, which has been provoked by fear of negative judgment, lack of confidence, and social comparison, causes significant disruptions in fluency, vocabulary recognition and the desire to speak. On the same note, difficulties of high thinking, including complicated grammar processing, real-time speaking multitasking, explaining instructions, and vague instructions strain working memory and declines speaking performance. This paper also determines the major coping options among the students and they are preparation, relaxation, positive self-talk, peer support and in a few instances resignation. In sum, the study demonstrates the necessity of favourable classroom conditions, minimal extraneous cognitive demands and anxiety-decreasing pedagogic interventions in order to enhance English speaking proficiency during the university stage. The results present useful implications to teachers, curriculum developers and language instructors as a way of tailoring more effective and psychologically accommodating learning experiences.